Waqf fundraising through money in the industrial revolution 4.0 era: A case study on Baitulmaal Munzalan Indonesia - Bustami Bustami; Rio Laksamana; Zuliana Rofiqoh (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2020)
Only a few institutions are professionals in managing waqf in West Kalimantan Province. Baitulmaal Munzalan Indonesia Foundation (BMI) is present as one solution for people who want to donate their fund’s waqf through money in the industrial revolution 4.0 era. Having only been established for three years, BIM has managed to raise funds cash waqf of Rp. 2.9 billion. This paper aims to explain the strategies and constraints faced by BMI in collecting endowment funds through money in the digital age. By using the type of field research and data collection techniques through observation, interviews, and Focus Grup Discussion (FGD), there are two research results in this paper. First, the strategies used by BMI in developing cash waqf in the digital age are companies through social media (Facebook pages and Instagram) and tablig. Kampanye through social media is the most dominant strategy used by BMI and has enormous potential. Secondly, the obstacle felt by BMI in managing and developing cash waqf is negative perceptions from the community (external obstacle). Based on the results of this study, the authors argue that marketing through social media not only has positive implications for for-profit institutions but also non-profit institutions such as BMI in collecting and managing cash waqf in Indonesia.